Experiências de leitura no universo virtual: a influência do booktuber - Martinelli, Eduarda Vieira (2020)
This dissertation deals with the growth of the role and influence of the booktuber as a mediator of readings and an influencer of habits in a community that establishes itself around it, just to discuss books. We defend the role of the school and the teacher as the main mediators of reading habits, while recognizing that the Internet, being present in the most varied aspects of socialization and the dissemination of information and knowledge, enables changes in the conventional structures of the literary system. For this, the dissertation is divided into two theoretical chapters, which explain the main research concepts. The first chapter, entitled “Literature and reading: expanded systems”, will demonstrate the history of the Internet, while conceptualizing virtual communities. The design of the traditional literary system will also be mobilized, questioning it and presenting its updates, such as the literate system and the polysystems. In order to understand the role of the reading mediator and the reader himself, the types of readers presented by Lúcia Santaella (2013) will be observed. The second theoretical chapter, on the other hand, observes the role of the teacher as a mediator in a world dominated by the virtual, explaining that the relationship between book and reader is established through experience, according to Jorge Larrosa (2014). It is noticed that the main point of the formation of readers and the renewal of reading skills is given in the sharing of the experience caused by literature, allowing anyone who crosses the sea of experience - be it booktuber or teacher - to be able to inspire others to read and discuss literature. After the theoretical chapters, we will analyze nine comments found in three different booktubers channels, in order to verify their influence on the reading habits of their subscribers. These comments will be removed from the channels “Literature-se”, by Mell Ferraz; “Ler Antes de Morrer”, by Isabel Lubrano; and “Pam Gonçalves”, which bears the same name as its creator. In this way, we will conclude that the influence of internet video creators who discuss books is true and trains readers, in addition to modifying and maintaining literary habits among individuals who participate in their online community.